2021
DOI: 10.1021/acs.jnatprod.1c00565
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products with Potential for Nonhormonal Male Contraception

Abstract: Despite increased access to contraception over the last 60 years, unplanned pregnancies continue to contribute to economic disparities and overpopulation. Additionally, the burden of family planning falls primarily on women, as a reliable pharmaceutical male contraceptive has yet to be developed. The objective of this literature-based systematic review was to identify compounds for future study from natural sources with potential nonhormonal male contraceptive activity. After the exclusion of extracts and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 87 publications
1
2
0
1
Order By: Relevance
“…Wang et al (1987) reported that gossypol is an anti‐fertility compound; 30 mg/kg of orally administered (−)‐gossypol for 7 days adversely influenced rat fertility (Wang et al, 1987) by causing azoospermia (spermless ejaculation) in males (Coutinho, 2002). This finding is consistent with those of Shunnarah et al (2021), who reported that gossypol stifles reactions in the acrosomes of human and mammal sperms (Shunnarah et al, 2021). Notwithstanding its usefulness as a bioactive contraceptive, it has serious ramifications, such as irreversible sterility, anorexia, and respiratory disorders (Lim et al, 2019).…”
Section: Chemistry Toxicity and Bioactivity Of Gossypolsupporting
confidence: 92%
“…Wang et al (1987) reported that gossypol is an anti‐fertility compound; 30 mg/kg of orally administered (−)‐gossypol for 7 days adversely influenced rat fertility (Wang et al, 1987) by causing azoospermia (spermless ejaculation) in males (Coutinho, 2002). This finding is consistent with those of Shunnarah et al (2021), who reported that gossypol stifles reactions in the acrosomes of human and mammal sperms (Shunnarah et al, 2021). Notwithstanding its usefulness as a bioactive contraceptive, it has serious ramifications, such as irreversible sterility, anorexia, and respiratory disorders (Lim et al, 2019).…”
Section: Chemistry Toxicity and Bioactivity Of Gossypolsupporting
confidence: 92%
“…Rata-rata morfologi abnormal spermatozoa paling banyak ditemukan pada mencit dengan perlakuan dosis tertinggi (P3) yaitu 66,00% dan paling sedikit ditemukan pada perlakuan kontrol (P0) yaitu 19,20%. Hal ini dapat terjadi dikarenakan adanya senyawa alkaloid pada biji klabet yang diduga dapat menurunkan kadar enzim antioksidan yang menyebabkan peningkatan Reactive Oxygen Species (ROS) di epididimis, sehingga dapat mengganggu pematangan dan penyimpanan spermatozoa menyebabkan spermatozoa abnormal (Shunnarah et al, 2021). Menurut penelitian Susilawati et al (2022) yang menunjukkan terjadinya kenaikan spermatozoa yang abnormal.…”
Section: Kualitas Spermatozoaunclassified
“…Gossypol inhibits the acrosomal reactions of human and mammalian sperm. 56 In 1978, Chinese scientists announced that oral gossypol was used as a reversible male infertility agent. Gossypol was effective in antifertility, 0.3 mg kg −1 of body weight caused azoospermia.…”
Section: Bioactivitymentioning
confidence: 99%